Uterine disorders and pregnancy complications: insights from mouse models - Lim, Hyunjung Jade; Wang, Haibin (The Journal of Clinical Investigation, 2010)
Much of our knowledge of human uterine physiology and pathology has been extrapolated from the study of diverse animal models, as there is no ideal system for studying human uterine biology in vitro. Although it remains debatable whether mouse models are the most suitable system for investigating human uterine function(s), gene-manipulated mice are considered by many the most useful tool for mechanistic analysis, and numerous studies have identified many similarities in female reproduction between the two species. This Review brings together information from studies using animal models, in particular mouse models, that shed light on normal and pathologic aspects of uterine biology and pregnancy complications.